Legal Nature of Reproducing Museum Objects in the Digital Form of NFT - V. D. Burdova (Journal of Digital Technologies and Law, 2023)
Objective: by revealing the legal nature of the nonfungible token (NFT), to propose a solution for the topical issues of legal regulation of relations emerging in the sphere of online market and Internet platforms, associated with reproduction and further use in the virtual environment of tokenized digital copies of original pieces of art.Methods: the research was based on formal-legal and comparative-legal analysis, applied together with methods of law interpretation.Results: a conclusion is made that reproduction of a museum object in the digital form of NFT is not equal to reproduction of a museum object in the simple digital format, as it does not contain such mandatory criteria as uniqueness, indivisibility and scarcity of the specific token. An NFT object acts as a digital original of an analog original of a museum object in the digital environment and the metaverse, not as a new form of media art. Expressed in the form of a uniqueness certificate of a digital object, an NFT object, by its legal nature and for the purpose of legal regulation of deals with it, refers to “other property” among the objects of civil law, which allows the museums to apply the respective contract constructs when structuring such deals.Scientiﬁc novelty: the author proposes a new approach to considering and improving the legal regulation, accounting and storing NFT objects as virtual museum objects, the so-called digital equivalents of an item, which possess the signs of individual-definite character and uniqueness, differing from simple digital copies, digital pieces of art, 3D mapping, etc.Practical signiﬁcance: the research results can be used for improving legal regulation of museum activity, correcting the civil and museum legislation, in particular, for defining virtual museum objects; for implementation of law, for example, when signing deals on using and selling NFT objects, in terms of specifying the content and volume of authorities of the right holders of the nonfungible token.